The Holistic Perspective of the INCISIVE Project—Artificial Intelligence in Screening Mammography - Lazic, Ivan; Agullo, Ferran; Ausso, Susanna; Alves, Bruno; Barelle, Caroline; Berral, Josep Ll; Bizopoulos, Paschalis; Bunduc, Oana; Chouvarda, Ioanna; Dominguez, Didier; Filos, Dimitrios; Gutierrez-Torre, Alberto; et al. (My University, 2022)
Finding new ways to cost-effectively facilitate population screening and improve cancer diagnoses at an early stage supported by data-driven AI models provides unprecedented opportunities to reduce cancer related mortality. This work presents the INCISIVE project initiative towards enhancing AI solutions for health imaging by unifying, harmonizing, and securely sharing scattered cancer-related data to ensure large datasets which are critically needed to develop and evaluate trustworthy AI models. The adopted solutions of the INCISIVE project have been outlined in terms of data collection, harmonization, data sharing, and federated data storage in compliance with legal, ethical, and FAIR principles. Experiences and examples feature breast cancer data integration and mammography collection, indicating the current progress, challenges, and future directions.
Keywords: Medical images; Mammography; Artificial intelligence; Deep learning; Health data sharing